2008
DOI: 10.1016/j.chroma.2008.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Solid-phase microextraction method for the determination of volatile compounds associated to oxidation of fish muscle

Abstract: A procedure for the determination of volatile compounds derived from lipid oxidation of fish muscle samples is presented. Analytes are concentrated on a solid-phase microextraction fiber employed in the headspace mode (HS-SPME), and selectively determined using gas chromatography in combination with mass spectrometry (GC-MS). The influence of several parameters on the efficiency of microextraction such as type of fiber, volume of sample, time, temperature, salting-out effect and stirring was systematically inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
132
0
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(146 citation statements)
references
References 36 publications
7
132
0
7
Order By: Relevance
“…This method provides many advantages over other ones, including easy manipulation and experimental set up, short sampling times, easy automation and high sensitivity [81]. A number of authors have applied this method for food lipid oxidation determinations [80,82]. Its main drawback is that fibre degradation and contamination occurs quite rapidly, thus replacement is required periodically.…”
Section: Volatilesmentioning
confidence: 99%
“…This method provides many advantages over other ones, including easy manipulation and experimental set up, short sampling times, easy automation and high sensitivity [81]. A number of authors have applied this method for food lipid oxidation determinations [80,82]. Its main drawback is that fibre degradation and contamination occurs quite rapidly, thus replacement is required periodically.…”
Section: Volatilesmentioning
confidence: 99%
“…In contrast, use of antioxidants effectively inhibited the formation of this compound in the oil studied (Table 2). This compound is formed by the action of the 15-lipoxygenese on EPA (20:5 n-3) (IGLESIAS & MEDINA, 2008). Volatile compounds such as 1-penten-3-ol, and 2,4-heptadienal have been identified in fish oil (HSIEH et al, 1989) and associated in the oxidation process, as contributors of off-flavors.…”
Section: Volatile Compoundsmentioning
confidence: 99%
“…It has been shown that ray liver constitutes a rich source of ω-3 fatty acids, with EPA + DHA contents similar to cod oil and other marine species (NAVARRO-GARCIA et al, 2010). Thus, ray (Rhinoptera bonasus) liver oil could be used as an alternative source for ω-3 PUFA´s; however, due to the high degree of instauration of these oils, special care has to be taken in order to avoid lipid oxidation and rancidity, which can affect its shelf life (IGLESIAS & MEDINA, 2008). In order to avoid this problem, antioxidants have been commonly used as an indispensable tool to improve the oil shelf life (BARTEE, Navarro-García et al et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This result suggested that hydrolysis of gelatin during extraction could reduce the hydrolysis time at high temperature, leading to the lower abundance of volatile lipid oxidation products. Iglesias and Medina (2008) reported that propanal, 1-penten-3-ol, 2,3-pentanedione, hexanal and 1-octen-3-ol were the main volatile compounds formed during the storage of Atlantic horse mackerel muscle at 4°C. Varlet et al (2006) reported that carbonyl compounds including 4-heptenal, octanal, decanal, and 2,4-decadienal were responsible for the fishy odour of salmon flesh.…”
Section: Volatile Compounds Of Gelatin Hydrolysatementioning
confidence: 99%
“…Volatile compounds in gelatin hydrolysate samples were determined using solid-phase microextraction gas chromatography mass spectrometry (SPME-GC-MS) following the method of Iglesias and Medina (2008) with a slight modification.…”
Section: Volatile Compoundsmentioning
confidence: 99%